Syndrome Differentiation and Mechanism Exploration of “Tongguan Liqiao” Acupuncture Method for Treating Poststroke Dysphagia - Hongwen Huang; Chao Chen; Xiaonong Fan (Chinese Medicine and Natural Products, 2024)
“Tongguan Liqiao” acupuncture method established by Xuemin Shi, a master of traditional Chinese medicine in China and academician of the Chinese Academy of Engineering, derives from the famous “Xing Nao Kai Qiao” therapy (activating the brain and opening the orifices) acupuncture method. It fundamentally takes “adjusting the spirit” as the root of selecting acupoints based on syndrome differentiation. Neiguan (PC 6), Renzhong (DU 26), and Sanyinjiao (SP 6) are selected as the main acupoints to adjust the spirit and revive the brain, nourish the liver and kidney, which treats the root cause. Acupoints such as Lianquan (RN 23), Yifeng (SJ 17), Wangu (GB 12), and Fengchi (GB 20) in the neck region are selected for “unblocking orifices,” which relieves the symptoms. This acupuncture method features deep needling, which aligns with modern swallowing function anatomy. The method can improve the function of poststroke dysphagia by enhancing cerebral blood supply and metabolism and promoting neural functional remodeling.